The U.S. Army in Asia, 2030-2040 - Kelly, Terrence K. (RAND Corporation, 2014)
Looking to the 2030-2040 time frame, U.S. policy and military strategy will need to strike a balance among maintaining a cooperative relationship with China, deterring Chinese aggression in regional disputes, and preparing for the possibility that China could become more assertive. The U.S. Army will have an important role to play in preparing for these developments and for protecting and furthering U.S. interests in the region.